Association of Frailty and the Expanded Operative Stress Score with Preoperative Acute Serious Conditions, Complications, and Mortality in Males Compared to Females: A Retrospective Observational Study. Issue 2 (10th February 2023) - Yan, Qi; Kim, Jeongsoo; Hall, Daniel E.; Shinall, Myrick C.; Reitz, Katherine Moll; Stitzenberg, Karyn B.; Kao, Lillian S.; George, Elizabeth L.; Youk, Ada; Wang, Chen-Pin; Silverstein, Jonathan C.; Bernstam, Elmer V.; et al.
Abstract : Objective: The aim of this study was to expand Operative Stress Score (OSS) increasing procedural coverage and assessing OSS and frailty association with Preoperative Acute Serious Conditions (PASC), complications and mortality in females versus males. Summary Background Data: Veterans Affairs male-dominated study showed high mortality in frail veterans even after very low stress surgeries (OSS1). Methods: Retrospective cohort using NSQIP data (2013–2019) merged with 180-day postoperative mortality from multiple hospitals to evaluate PASC, 30-day complications and 30-, 90-, and 180-day mortality. Results: OSS expansion resulted in 98.2% case coverage versus 87.0% using the original. Of 82, 269 patients (43.8% male), 7.9% were frail/very frail. Males had higher odds of PASC [adjusted odds ratio (aOR) = 1.31, 95% confidence interval (CI) = 1.21–1.41, P < 0.001] and severe/life–threatening Clavien-Dindo IV (CDIV) complications (aOR = 1.18, 95% CI = 1.09–1.28, P < 0.001). Although mortality rates were higher (all time-points, P < 0.001) in males versus females, mortality was similar after adjusting for frailty, OSS, and case status primarily due to increased male frailty scores. Additional adjustments for PASC and CDIV resulted in a lower odds of mortality in males (30-day, aOR = 0.81, 95% CI = 0.71–0.92, P = 0.002) that was most pronounced for males with PASC compared to females with PASC (30-day, aOR = 0.75, 95% CI = 0.56–0.99, P = 0.04). Conclusions: Similar to the male-dominated Veteran population, private sector, frail patients have high likelihood of postoperative mortality, even after low-stress surgeries. Preoperative frailty screening should be performed regardless of magnitude of the procedure. Despite males experiencing higher adjusted odds of PASC and CDIV complications, females with PASC had higher odds of mortality compared to males, suggesting differences in the aggressiveness of care provided to men and women.